Bilateral temporomandibular joint dislocations post-bronchoscopy in a case of paclitaxel-induced pneumonitis. Issue 2 (22nd February 2021) - Li, Anna; Mohammadi, Fadak; Crocker, Helen
Abstract : This case report presents the unusual complication of bilateral temporomandibular joint dislocation following bronchoscopy, highlighting the importance of recognising it as a differential diagnosis in patients having jaw symptoms. The delayed diagnosis in this case resulted in multiple unsuccessful reduction attempts under sedation, which added to the distress of the patient. Notably, the procedure yielded a rare diagnosis for the patient that intrinsically changed the management of her breast cancer.